Chapter Conclusions - Patzold, Steffen (Reti Medievali E-Book, 2022)
The summary highlights the extent to which the articles collected here go beyond previous research on bishops and open up new perspectives: The contributions no longer only ask about the "hard power" of bishops. Instead, they focus on episcopal "soft power": they impressively show that bishops knew how to use books, pen and ink to manipulate ideas and convictions and to reframe discourses. A basis for this new approach is provided by the scans of medieval manuscripts, which are now made available by libraries in Europe in large numbers and excellent quality.